Measuring Hotel Financial and Non-Financial Performance in Thailand: The Application of Technology-Organization-Environment (TOE) Framework - Yoopetch, Chanin; Chareanporn, Tarittawan (Journal of Ecohumanism, 2024)
Guided by the Technology-Organization-Environment (TOE) framework, the current study aims to test the impacts of organizational factors, technological factors, and environmental factors on the financial and non-financial performance (or goals) of hospitality firms. Unlike several empirical studies in the past, this study attempted to compare the effects of these factors on financial and non-financial performances. The authors proposed the contributions with clearer and more specific recommendations and a greater understanding of how managers can improve and adjust their strategic plan and implementation to achieve long-term firm performance. The data analysis was structural equation modeling. Prior to the data analysis, reliability and validity tests were conducted to certify the quality of the data. After screening the data carefully, based on 350 hospitality firms in Thailand, including 3–5-star hotels in Thailand representing all parts of the country, the results indicated that organizational factors and technological factors had significant effects on both financial and non-financial performance. The environmental factor demonstrated no significant effect on financial and non-financial performance. Moreover, for the theoretical contribution, this study provided empirical research by applying the TOE framework in the context of the hospitality industry, presenting that organizational factors and technological factors had significant impacts on the firm performance. Discussion with the past literature provided deeper insights into the findings. Research conclusions and practical recommendations were also provided.